Aerodynamic Performance of a Dragonfly-Inspired Tandem Wing System for a Biomimetic Micro Air Vehicle - Salami, Erfan; Montazer, Elham; Ward, Thomas A; Nik Ghazali, Nik Nazri; Anjum Badruddin, Irfan (Frontiers in Bioengineering and Biotechnology, 2022)
The flying agility demonstrated by dragonflies is accomplished by means of complex aerodynamic forces produced by flapping their four wings arranged in a tandem configuration. The current study presents a novel tandem flapping wing mechanism for a biomimetic air vehicle that was designed and manufactured to experimentally investigate the aerodynamic forces. By optimizing the configuration and using spatial network analysis, it is shown that the designed structure can flap the wings in a linear up–down stroke motion and is capable of maintaining good consistency and aerodynamic performance. Such a mechanism could be used in a future biomimetic micro air vehicle (BMAV) design. The mechanism uses an electromagnetic actuator to flap the wings with a variable beat frequency (30–210 Hz) at various angles of attack (−10°–20°). The results show that the tandem wings generate approximately 50% higher lift than the forewing or hindwing pairs acting alone. Tandem wings also improve stability, which could potentially allow hovering.